Analysis of Switched Reluctance Motor Behavior under Electrical Fault Conditions - Peter Dubravka; Pavol Rafajdus; Pavol Makys; Valeria Hrabovcova; Lorand Szabo (Communications, 2013)
This paper deals with analysis of Switched Reluctance Motor (SRM) behavior under fault conditions. The static parameters of the healthy SRM and SRM with defined faults of phases are investigated by Finite Element Method (FEM). These static parameters are used in dynamic simulation of the SRM. Transients are simulated for the healthy motor and for the motor under fault conditions. Results of the simulations are compared with experimental measurements.